Enhanced photoconversion efficiency in organic polymer solar cells: Synthesis, structural analysis and computational modelling of 4,8-dichlorobenzo[1,2-b]difuran-2,6-dicarboxylic acid-based composite - Ananthavalli, Raman; Karpagam, Jagadeesan; Ramalingam, Singaravelu; Aarthi, Ramadoss (European Journal of Chemistry, 2025)
Improving the photoconversion efficiency (PCE) of organic polymer-based solar cells (SCs) is crucial to their competitiveness with conventional SCs. This study presents a novel approach to improve PCE of an organic composite solar cell incorporating 4,8-dichlorobenzo[1,2-b]difuran-2,6-dicarboxylic acid. The molecular composite was designed based on the photoactive donor-π-acceptor (D-π-A) architecture and computationally modeled to optimize its efficiency. The synthesized material was characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), and spectral analysis, confirming the formation of a perovskite lattice. Photovoltaic performance was evaluated using simulated device measurements, which produced a fill factor (FF) of 0.708, a short-circuit current density (JSC) of 12.8 mA/cm2, an open-circuit voltage (VOC) of 1.22 V, and an overall PCE of 12.78%. The active exciton diffusion path length was measured at < 9 Å, with a direct band gap of 2.05 eV. The stabilized Urbach energy of the material ranged from 110 to 220 meV. Furthermore, the active single-layer film was interfaced with both a small work function electrode (SWFE) and a long work function electrode (LWFE). The material exhibited high polarizability (αtot = 483.34×10-33 esu, Δα = 332.68×10-33 esu), indicating a strong potential for efficient photoconversion. This study demonstrates the feasibility of using 4,8-dichlorobenzo [1,2-b] difuran-2,6-dicarboxylic acid-based composite for high-performance organic solar cells, offering a promising alternative to conventional SCs.